Pendidikan Anak dalam Lingkup Keluarga Menurut Al-Qur’an - Ade Salamun; Didin Hafidhuddin; Akhmad Alim (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
The modern era has an impact on the decline in the function of the family in children's education, even though the family has a very important function in the formation of children's character. The hadith of the Prophet SAW also said, "Honor your children and correct their manners". The purpose of writing this article is to provide an overview of the methods of child education in the family sphere according to the Qur'an. The method used in writing this article is a literature method with a descriptive analysis approach that uses data sources in the form of books, scientific journals, laws, theses, and dissertations. Based on the results of the analysis, it is known that in the stages of child development, before a child enters the world of formal education, the family (parents) becomes the first educational environment for a child so that parents must be a good role model for their children as the Prophet SAW who became a role model for his people. Therefore, it can be concluded that the method of educating children in the family environment according to the Qur'an is exemplary.